Knowledge and practices of vegetable consumption in Accra and greater Lomé: nutritional, health and environmental sustainability - Elom Assinou, Kokou; Kpotchou, Koffi (Edelweiss Applied Science and Technology, 2024)
In Accra and Greater Lomé, research into the harmful effects of food transitions focuses scarcely on the levels of knowledge and good practices (LKGP) of vegetable consumers. However, these foods play a key role in the nutritional, health, socio-economic and ecological sustainability of cities. This research aims to assess the health, nutritional, ecological and socio-economic sustainability of LKGP linked to vegetable consumption in these conurbations. A quantified multi-criteria evaluation approach was adopted. The respondents (394), selected via judgmental sampling, were equally distributed between the two cities. Data were collected using a Food Frequency Questionnaire administered by Kobocollect. The overall average rate of good vegetable consumption knowledge and practices in Accra and Greater Lomé is low (37.43%). This result stems from the low LKGP for daily vegetable consumption (24.62%), their inclusion in the main daily meals (33.50%) and consideration of their nutritional composition (30.86%). The target population is unaware of the health, nutritional and ecological drawbacks of poorly preserved vegetables (66.93%) and adopts inappropriate waste management practices when handling them (65.91%). The average proportions of access to vegetable procurement technology (47.08%) and sustainable food education (11.29%) were also low. The research results, unfavorable to the achievement of the SDGs in Accra and Greater Lomé, call for an inclusive, integrated and continuous sustainable food education program.